Teacher’s Scaffolding in Academic Reading and Writing by Using SmallGroup Discussion in University level - Asti Rahmiadji; Henda Hendardi; Zihan Fauziah Meilani; Yustika Nur Fajriah (Institut Pendidikan Indonesia Garut, 2023)
The use of scaffolding in many teaching subjects has been used by teachers. Many lectures use scaffolding to embrace the students and make easier the learning. Lectures also use micro-scaffolding and macroscaffolding for teaching. Previous study said that using scaffolding has advantages and disadvantages. However, this article attempts to find out the result of using scaffolding in Academic Reading and Writing in classroom. This study using qualitative with case study as a path to gain the information, with an English lecturer in one of university in Garut. This study also used non-participant observation as instrument and gathering the information using inductive analysis. The finding indicate that scaffolding make the classroom interact each other.